Pelatihan Pembuatan Bahan Ajar Berbasis Kearifan Lokal Bagi Guru Sekolah Dasar di Desa Greged Cirebon - Haryanti, Yuyun Dwi; Yanto, Ari; Mahpudin, Mahpudin; Yonanda, Devi Afriyuni; Putri, Imel Amelia; Hendraman, Muhammad Maldini (P3M Politeknik Negeri Jember, 2025)
Local wisdom can be inherited from generation to generation because it plays an important role in preserving the cultural identity of the community in the midst of the rapid pace of modernization and globalization. Teachers play an important role in integrating learning with local wisdom of the local area through teaching materials. Indonesia has a wealth of important local traditions and wisdom and must be preserved from negative external influences. Local values function to maintain the welfare of the Indonesian people in the current era. Community service activities were carried out for 20 teachers at SD Negeri 1 Sindang Kepeng, Greged District, Cirebon Regency, West Java. Training in making teaching materials based on local wisdom utilizes the use of the canva application. The service method used in this activity consists of 3 stages, namely planning, implementation, and evaluation. The training process went well from the beginning to the end of the activity. Training activities include: pretest, material delivery, training, postest, evaluation and reflection. This training can increase teachers' knowledge and competence in designing and producing teaching materials for local wisdom using the Canva application.